Turvallisuus ja kilpailukyky: Kansainvälisten kilpailukykymittareiden valossa - Tuomas Möttönen (The Research Institute of the Finnish Economy (ETLA), 2004)
Raportissa tarkastellaan turvallisuuden ja kilpailukyvyn välisiä yhteyksiä kansainvälisten kilpailukykyindikaattoreiden valossa. Raportti on laadittu uusimman vuonna 2003 ilmestyneen World Economic Forumin (WEF) ja vuonna 2004 ilmestyneen International Institute for Management Development -järjestön (IMD) raporttien pohjalta sekä muutoksina yli ajan vuodesta 1997 lähtien. Selvityksen kohteena ovat sekä koko maaaineisto että erikseen Suomelle tärkeät EU25-maat, Venäjä ja Yhdysvallat. Raportissa arvioidaan lyhyesti myös ulko- ja turvallisuuspoliittisten ratkaisujen vaikutusta kilpailukykyyn. Raportin mukaan turvallisuudella ja kilpailukyvyllä on selvä positiivinen yhteys. Kilpailukykyiset maat ovat myös turvallisia. Myös turvallisuuden osatekijöillä on raportin mukaan suora yhteys maan kilpailukykyasemaan. Sisäisen ja ulkoisen turvallisuuden kehittäminen on myös Suomen elinkeinoelämän tulevan menestymisen kannalta tärkeää. – – This report discusses the relationships between security and competitiveness in the light of global competitiveness indicators. This study is based mainly on the newest competitiveness reports. These are: World Economic Forums (WEF) “Global Competitiveness Report 2003” and International Institute for Management Developments “IMD World Competitiveness Yearbook 2004”. Also this report analyses recent security development from the year 1997. Particular focus is given to the most important trade partners of Finland, which are the EU25-countries, United States of America, Russia and China. The report also includes a short analysis of, how foreign and security policy decisions affect the competitiveness level of various countries. This study shows clearly that there is a strong positive connection between security and competitiveness. A competitive country is also a secure country. The individual security components have a direct connection to the countrys entire competitiveness position, so improving the Finnish internal and external security is important for the prospects of the Finnish economy in the future.
Keywords: 330; Turvallisuus; kilpailukyky; taloudellinen kasvu; Security; competitiveness; economic growth; Internationaler Wettbewerb; Wirtschaftswachstum; Sicherheitspolitik